2020
DOI: 10.21037/apm.2020.03.24
|View full text |Cite
|
Sign up to set email alerts
|

Personal instruction for patients before colonoscopies could improve bowel preparation quality and increase detection of colorectal adenomas

Abstract: Background:To analyze whether face-to-face education before colonoscopy improves the quality of bowel preparation and increases the detection of adenomas.Methods: A retrospective cross-sectional study of adult patients with colorectal polyps identified by colonoscopy as outpatients was performed. The patients underwent an added colonoscopy inpatient for resection of colorectal polyps. As outpatients, we gave the patients written bowel preparation instructions; however, when they were inpatients, we supplied fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…They were monitored (e.g. pulse, blood pressure, oxygen saturation) for the duration of the procedure [9] .…”
Section: Methodsmentioning
confidence: 99%
“…They were monitored (e.g. pulse, blood pressure, oxygen saturation) for the duration of the procedure [9] .…”
Section: Methodsmentioning
confidence: 99%
“…This improves compliance and ensures a successful colonoscopy by directly addressing the patient's expectations and the timetable for bowel preparation. 39 Ideally, when preparing for a colonoscopy, it is important to take into account patient variables such as past medical and surgical history, weight and compliance to the preparation.…”
Section: Preparation For Colonoscopymentioning
confidence: 99%
“…Studies have shown that using this teaching strategy rather than just giving out pamphlets or handouts alone results in a more effective bowel preparation. This improves compliance and ensures a successful colonoscopy by directly addressing the patient's expectations and the timetable for bowel preparation 39 …”
Section: Part I: Introductionmentioning
confidence: 99%
See 1 more Smart Citation